PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) DALAM MENGEMBANGKAN KETERAMPILAN KOMUNIKASI PESERTA DIDIK PADA PEMBELAJARAN SEJARAH SECARA DARING (Studi Deskriptif Kualitatif Di Kelas XI MIPA 1 SMAN 14 Bandung) - Dian Nuraeni Hidayah, - (2021)
This research is entitled "Application of Think Talk Write (TTW) Cooperative Learning Model in Developing Students' Communication Skills in Online History Learning (Study of Qualitative Descriptive in Class XI MIPA 1 SMAN 14 Bandung). The purpose of this research is to describe how the process of planning, implementing, to finding obstacles and solutions sought by the teacher in implementing the learning model. This research is motivated by the existence of a condition concerning the decreased students' communication skills in history learning which is carried out online during the pandemic. This condition was then responded by the teacher by implementing a learning model which was then developed by utilizing the breakout room feature in the zoom meeting platform. The application of the model then attracted the researchers' attention to see and describe more deeply about how the application of the think talk write type of cooperative learning model was carried out by the teacher in an effort to develop students' communication skills in online history learning. This research is a study of qualitative descriptive in class XI MIPA 1 SMAN 14 Bandung. Data collection techniques were carried out through observation, interviews, and documentation studies. From the results of the research that has been done, it can be seen that communication skills with indicators developed, namely interaction in groups, written submissions, conveying ideas, and providing responses can be developed quite well although not fully maximized. The results of research regarding the applies of a think talk write type of cooperative learning model can be one solution that can be applied in an effort to develop students' communication skills in online history learning, with a note that teachers must maximize learning tools, and pay attention to several important components in online learning such as means of and infrastructure that can support during the learning process, so that the application of the model can be carried out properly.